MOF-in-COF molecular sieving membrane for selective hydrogen separation - Hongwei Fan (Nature Portfolio, 2021)
Covalent organic frameworks (COFs) are promising materials for separation membranes, but their wide pores prevent selective gas separation through molecular sieving. Here, the authors demonstrate a Metal-organic framework (MOF)-in-COF membrane with a significant enhancement of separation selectivity of hydrogen over other gases.